Utilising Digital Image Correlation for the Characterisation of Ground Shock from Buried Charges - Waddoups, Ross (Cranfield University, 2024)
Paper presentation to the Defence and Security Doctoral Symposium 2023
Keywords: DSDS23; Blast; Soil; Ground shock; DIC; Digital Image Correlation; DSDS23 Paper Presentation